Wie generisch ist das generische Maskulinum? Über Genus und Sexus im Deutschen - Trutkowski, Ewa (ZAS Papers in Linguistics, 2018)
This paper examines whether gender features (masculine, feminine, neuter) in German have to be interpreted semantically, along their specific gender, or whether they allow for a gender unrelated interpretation. As to this, two experiments with two different classes of nouns (gender marked and sex marked nouns vs. gender marked and sex neutral nouns) were conducted. The first experiment supports the view that in their function as nominal predicates masculine nouns, contrary to feminine (and neuter) nouns, have the widest extension – which confirms the existence of a ‘Generic Masculine’ (Generisches Maskulinum). On the other hand, the second experiment shows that in their function as subjects masculine nouns, contrary to feminine (and neuter) nouns, are the least flexible agreement controllers – hardly allowing for gender mismatches. Thus, masculine nouns behave differently depending on whether they appear as controllers/sources of agreement or as targets of agreement. The findings are supplemented by corpus data.